# Yahoo Web Search

1. ### sin3y/siny=1+2cos2y prove LHS =RHS?

sin3y/siny = sin(y+2y) / siny = ( sinycos2y + cosysin2y) / siny Using sin2y = 2sinycosy = [ sinycos2y + 2siny(cosy)^2 ] / siny = siny[ cos2y + 2(cosy)^2 ] / siny = cos2y + 2(cosy)^2 = cos2y + 2(cosy)^2 - 1 + 1 Using cos2y = 2(cosy)^2 - 1 = cos2y + cos2y + 1 = 2cos2y + 1

3 Answers · Science & Mathematics · 28/12/2008

2. ### Which postulate or theorem can you use to prove < LHS ≅ <THS?

Note that the side in the middle is shared by both triangles. This means that that side is congruent for both triangles as well. Since we have two sides congruent already and the side shaded is congruent, all 3...

2 Answers · Science & Mathematics · 25/04/2010

3. ### LHS =RHS How To Solve This ?

the trick is to multiply the numerator&denominator of the right side by (1-sinθ) to get 1-sin(θ)^2 that way you can convert to cos(θ)^2 then you break the fraction into two look here: http://i279.photobucket.com/albums/kk124/firelilee/img475.jpg

4 Answers · Science & Mathematics · 03/03/2009

4. ### Prove tht LHS =RHS:sinA/secA+tanA-1+cos/cosecA+cotA-1=1?

sec=1/sin cosec=1/cos cot=1/tan=cos/sin sina/1/sina+cosa/sina-1+cosa/1/cosa+cosa/sina+1= 1. sin^2a+sina/cosa+cosa/sina-1+cos^2a+1=1 (sin^2a+cos^2a)+(sin^2a+cos^2a)/coasina-1=1 1+(cos^2a+sin^2a-1=1 1-1+(sin^2a+cos^2a=1sin^2a+cos^2a=1.

2 Answers · Science & Mathematics · 26/05/2008

5. ### Can you prove from RHS = LHS especially in a HSC exam?

why should one be penalized if you showing the two sides are equal ? Typically we start with the more complicated side and it usually is on left.

3 Answers · Science & Mathematics · 11/01/2014

6. ### Verifying that LHS and RHS are equal. (sinX / (1+cosX) ) + (cosX/sinX) = cscX?

Your first equation, using parentheses, is better. Yahoo!Answers doesn't lend itself to vertical fractions! Use the Pythagorean Identity sin²θ = 1-cos²θ...

1 Answers · Science & Mathematics · 14/10/2016

7. ### (1+cos2A)/cos2A = Tan2A/tanA prove LHS - RHS?

If you mean cos(2A) then (1+cos2A)/(cos2A) = Tan2A/tanA 1+cos2A=tan2A*cos2A/tanA 1+cos2A=sin2A/tanA 1+cos2A=(2*sinA*cosA)/(sinA/cosA) 1...

1 Answers · Science & Mathematics · 07/05/2008

8. ### Show that a^loga b = b please use LHS =RHS ?

take log(base a) both sides

3 Answers · Science & Mathematics · 04/08/2012

9. ### Prove : manipulate LHS and RHS (1/cos(x) - tan(x))^2 = 1-sin(x)/1+sin(x)?

http://www.openaspdf.com/files/735057/WolframAlpha--_1_cos_x____tan_x___2____1_sin_x____1_sin_x____Result__2014_03_06_0259.pdf

2 Answers · Science & Mathematics · 11/03/2014

10. ### Use any mathematical expression like (+,-, /, *, etc) and convert the LHS value to RHS in two ways. 0 0 0?

( 0! + 0! + 0! + 0! ) ! = 24 ( (0! +0!) ^ (0! +0!) ) ! = 24

1 Answers · Science & Mathematics · 08/07/2008